Communication Behaviour of Traditional Fishermen - S., Balasubramaniam; Mohan, Braj; M.K., Kandoran (Fishery Technology, 2025)
This paper analyses the communication behaviour of traditional fishermen operating motoriscd andÂ·non-motoriscd crafts. The results revealed that among the 12 independent viariables, technological gap variable had negative correlation with the communication behaviour of fishermen operating motoriscd crafts. For the fishermen operating non- motoriscd crafts, information need had positive correlation and the variable, experience, had significant positive influence on their communication behaviour. Further, the results revealed the socio-pcrsonal and technological characteristics of fishermen who had low and high communication behaviour scores.